PENGARUH KUALITAS DOSEN DAN METODE MENGAJAR TERHADAP PEMAHAMAN AKUNTANSI (STUDI KASUS MAHASISWA PRODI AKUNTANSI UNIVERSITAS RIAU KEPULAUAN BATAM) - Ryan Hidayat; Ravika Permata Hati (Universitas Riau Kepulauan, 2017)
Quality of faculty and teaching methods to the Understanding accounting (a case study studebt university accounting university of the riau islands of batam)This study aimed to analize whether quality of faculty and teaching methods on Understanding accounting student. This study uses a survey method using primary data obtained from questionnaires. The number samples taken in this study were 70 students of accounting courses university of riau islands of batam.The results obtained by calculation have been done, for quality of faculty of t test for ( 3.006), while t table for ( 1.998) (t test t table) at a significance level of 0,000, this show that quality of faculty has a significant positive effect Understanding of accounting and the teaching methods of t test at (6.973) while the t table (1.998) ( t test t table) at a significance level of 0,000 mean the teaching methods have a positive influence significantly to the Understanding of accounting.Quality of faculty and teaching methods Simultaneously have a significant positive influence on the Understanding of accounting students with F-test value of 35.339, while the F-table 3.130 (F-test F-table) with a significant level of 0.00.